Electrocardiogram in Chagas disease - Brito,Bruno Oliveira de Figueiredo (2018)
Abstract Since the initial descriptions of Chagas cardiomyopathy (ChCM), the electrocardiography has played a key role in patient evaluations. The diagnostic criterion of chronic ChCM is the presence of characteristic electrocardiographic (ECG) abnormalities in seropositive individuals, regardless of the presence of symptoms. However, these ECG abnormalities are rarely specific to ChCM and, particularly among the elderly, can be caused by other simultaneous cardiomyopathies. ECG abnormalities can predict the occurrence of heart failure, stroke, and even death. Nevertheless, most prognostic studies have included Chagas disease (ChD) populations and, not exclusively, ChCM. Thus, more studies are required to evaluate the efficacy of ECG in predicting reliable prognoses in established chronic ChCM. This review exclusively discusses the role of the 12-lead ECG in the clinical evaluation of chronic ChD.